Implementation of Smart Governance in Smart Villages - Shelly Noer Anggraeni; Eny Haryati; Dian Ferriswara (Perspektif Administrasi Publik dan hukum, 2025)
This study aims to describe and analyze: how to implement smart governance in smart villages. The type of research used is qualitative research. The data analysis technique in the study uses techniques developed by McNabb (2002), namely Grouping the data according to key constructs, Identifying bases for interpretation, Developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the implementation of smart governance in the Three Villages Government as a Smart Village in Sidoarjo Regency is measured based on 3 aspects, namely: public service aspects, village information system aspects, and village fund management aspects. Information technology is indispensable in the implementation of all aspects of smart governance, both public services, village information systems, and village fund management. The first aspect is that public services can be faster and more optimal with the implementation of smart governance. Previously, village people who wanted to take care of village administration needs had to travel a considerable distance from their village to the sub-district center and even the district center, so it took extra time and energy to take care of it. After the online service, all village administration needs can be done quickly and easily because they can be directly verified by sub-district and district officers without having to visit the sub-district or district office. The second aspect is that village information can be obtained by the community at large easily and quickly. Previously, village people who wanted to know information about their village had to visit the village office.